An oscillatory component of the H-reflex. Issue 3 (March 1981) - Crayton, J W; Rued, R R
Abstract : H-reflex recovery curves studied in 57 normal volunteers could be divided into three groups: one with sinusoidal properties having one or more periods, one having primarily linear or exponential properties, and a third, indeterminate group.